The impact of the Maputo Protocol in selected African states - Mutambasere, Susan; Budoo-Scholtz, Ashwanee; Murden, Davina (Pretoria University Law Press (PULP), 2023)
This book assesses the impact and effectiveness of the Protocol to the African Charter on Human and Peoples' Rights on the Rights of Women in Africa (Maputo Protocol) in 16 state parties. These countries are: Burkina Faso, Cameroon, Côte d'Ivoire, the Democratic Republic of Congo, Ethiopia, Eswatini, the Gambia, Ghana, Kenya, Lesotho, Malawi, Mauritius, Nigeria, Sierra Leone, Tanzania, and Zimbabwe. Each of the chapters traces the impact that the Protocol has had on the policies, laws, court decisions, civil society activism, and legal education in the particular state. Each chapter also discusses the relationship of the state with the African human rights mechanisms. The book is an update of two prior volumes of essays, titled The impact of the African Charter and the Maputo Protocol in selected African states, published by PULP in 2012 and 2016, and edited by the Centre for Human Rights, Universityof Pretoria (Centre) and Victor Ayeni, respectively. The third edition, focused more narrowly on the Maputo Protocol, appears as the continent marks 20 years since the adoption of the Protocol on 11 July 2003. By 11 July 2023, 54 out of 55 African Union member states (with the exception of Morocco) have become party to the African Charter, and 44 of them have accepted the Maputo Protocol. The book is edited by and contains several chapters by alumni of the Master's in Human Rights and Democratisation in Africa programme of the Centre. The Centre intends to use this research as the basis for a continuously updated database on the impact of the African Charter and Maputo Protocol.